2008
DOI: 10.1152/ajpheart.00484.2007
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of late sodium current by Ca2+, calmodulin, and CaMKII in normal and failing dog cardiomyocytes: similarities and differences

Abstract: Augmented and slowed late Na + current (I NaL ) was implicated in action potential duration variability, early afterdepolarizations, and abnormal Ca 2+ handling in human and canine failing myocardium Objective was to study I NaL modulation by cytosolic Ca 2+ ([Ca 2+ ] i ) in normal and failing ventricular myocytes.Methods-Chronic heart failure was produced in 10 dogs by multiple sequential coronary artery microembolizations, 6 normal dogs served as a control. I NaL fine structure was measured by wholecell pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
110
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 50 publications
10
110
0
Order By: Relevance
“…[65][66][67] It is widely accepted that signalling through the Ca 2+ -CaM-CaMKII pathway facilitates the sodium current, especially its late component. 16,65,68 The Ca 2+ dependent regulation modifies mainly the inactivation of the sodium channels. Ca 2+ or CaM binding to the channel causes a~5 mV shift in the steady-state inactivation (SSI) towards more positive voltages.…”
Section: +mentioning
confidence: 99%
“…[65][66][67] It is widely accepted that signalling through the Ca 2+ -CaM-CaMKII pathway facilitates the sodium current, especially its late component. 16,65,68 The Ca 2+ dependent regulation modifies mainly the inactivation of the sodium channels. Ca 2+ or CaM binding to the channel causes a~5 mV shift in the steady-state inactivation (SSI) towards more positive voltages.…”
Section: +mentioning
confidence: 99%
“…With respect to late I Na during the action potential plateau, several studies have indicated that this current is increased in human and canine heart failure (209,211), possibly resulting from a slowing of inactivation kinetics and a shift of the voltage dependence of steady-state inactivation, as mediated by intracellular Ca 2ϩ /CaMKII signaling (140,214). (207,208), whereas I Ks but not I Kr was downregulated in all layers of the left ventricular myocardium in a canine model of tachycardiainduced heart failure (133).…”
Section: Role Of Cardiac Dynamics In the Generation Of Ventricular Armentioning
confidence: 99%
“…Direct interaction between cytoplasmic COOH terminus (CT) domain of Na v 1.1 with Na v ␤ 1 and Na v ␤ 3 has recently been demonstrated (39) and thus offers possible molecular mechanisms for I NaL modulation by Na v ␤ 1 found here (if similar interactions exist for Na v 1.5). The role of the CT to regulate Na v 1.5 inactivation has been recently suggested via the Ca 2ϩ -calmodulin-dependent interaction with the III-IV linker, responsible for the initial fast inactivation (1, 33), and has been elucidated for I NaL regulation (20). It has been also suggested that the Na v ␤ 1 subunit modulates Na v 1.5 inactivation via interaction with the microtubule cytoskeleton (4).…”
Section: Molecular Mechanisms Of I Nal Modulation By Na V ␤ 1 and Na mentioning
confidence: 99%